Coordination Aspects of an Effective Sprint Start - Borysiuk, Zbigniew; Waśkiewicz, Zbigniew; Piechota, Katarzyna; Pakosz, Paweł; Konieczny, Mariusz; Błaszczyszyn, Monika; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
The aim of the present study was to examine differences in the movement structure and the coordination aspects expressed by bioelectrical tension indicators between a group of experts/sprinters and a group of novices/students. A group consisted of 20 sprinters and a control group consisted of 35 master's physical education students. A 16-channel surface electromyography (14 muscles) and two cameras with recording speed of 250 frames/per second were used. Significant differences were found between reaction time (p<0.005) and time at 30 m of the covered sprinting distance (p<0.001) between the students and advance athletes. Furthermore, the sprinters activated the back foot (taking off the starting blocks) and the front foot (first ground contact) earlier, which correlated with the attained times at 5 (r=0.66) and 10 m (r=0.62) of the covered sprinting distance. The most important component of the sprint start, apart from the muscle strength of the legs, is the appropriate motor coordination, which greatly affects the generation of power in the legs at the right time and optimal duration.